2014
DOI: 10.4314/ijbcs.v7i4.15
|View full text |Cite
|
Sign up to set email alerts
|

Évaluation des propriétés antimicrobiennes de <i>Pterocarpus erinaceus</i. Poir (Faboïdeae) et <i>Daniellia oliveri</i. (Rolfe) Hutch. et Dalz (Caesalpinoïdeae), utilisées en médecine traditionnelle au Togo

Abstract: Cette étude s'est appuyée sur des données d'enquêtes ethnobotaniques effectuées dans la Région centrale du Togo dans un contexte de valorisation de la flore médicinale. L'étude a permis de ressortir la fréquente utilisation de Pterocarpus erinaceus et Daniella oliveri, dans le traitement de maladies infectieuses. Pour tester l'efficacité de ces deux plantes, des tests ont été effectués sur une bactérie, Staphylococcus aureus et une levure, Candida albicans, des germes souvent impliqués dans des infections. Des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 5 publications
1
9
0
2
Order By: Relevance
“…It has also been confirmed that its stem bark possesses a broad antimicrobial spectrum including Bacillus subtilis, Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus and Candida albicans [27][28][29]. Tittikpina et al [29] isolated four compounds from the plant, i.e. friedeline, 2,3 dihydroxypropyloctacosanoate, a mixture of βsitosterol stigmasterol and campesterol; βsitosteryl-β-D-glucopyranoside which were found to be active against bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been confirmed that its stem bark possesses a broad antimicrobial spectrum including Bacillus subtilis, Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus and Candida albicans [27][28][29]. Tittikpina et al [29] isolated four compounds from the plant, i.e. friedeline, 2,3 dihydroxypropyloctacosanoate, a mixture of βsitosterol stigmasterol and campesterol; βsitosteryl-β-D-glucopyranoside which were found to be active against bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Pterocarpus erinaceus contains tannins, flavonoids, phenols and saponins. It has also been confirmed that its stem bark possesses a broad antimicrobial spectrum including Bacillus subtilis, Pseudomonas aeruginosa, Escherichia coli, Staphylococcus aureus and Candida albicans [27][28][29]. Tittikpina et al [29] isolated four compounds from the plant, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The tree is widespread in the savannah areas that stretch from Senegal and Gambia to Chad and the Central African Republic [ 6 ]. The Tchamba tribe in Togo (which calls the tree “Boutô”) employs its bark to treat candidiasis and various other infections [ 7 , 8 ]. In contrast, the Kotokoli tribe in the same country, referring to the tree as “Tem”, uses powders obtained from its roots against typhoid fever and bark decoction against haemorrhoids [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This is hardly surprising given the high cost of orthodox medicines (Cameron et al, 2009), coupled with the fact that almost two-thirds of the population live in rural areas, and the country consists of 42 different ethnic groups, each with its very own traditions and rituals (Kuevi, 1981; Goeh-Akue and Gayibor, 2010). The extensive use of such plants -and products derived from them -in the treatment of various diseases has also resulted in different scientific studies, which have explored the diversity in the use of plants in Togo in general, and the regional folk medicine in particular (Agody, 2007;Moukaïla, 2010;Tchacondo et al, 2011;Amegan, 2012;Tittikpina et al, 2013;Franck, 2014;Zabouh, 2014;Sema, 2015;Lawson-Viviti, 2015).…”
Section: Plants As a Widely Used Natural Resource In Togomentioning
confidence: 99%